Systematic review: medical therapy for fibrostenosing Crohn's disease. Issue 12 (13th May 2020) - Lu, Cathy; Baraty, Brandon; Lee Robertson, Helen; Filyk, Alexis; Shen, Hua; Fung, Tak; Novak, Kerri; Ma, Christopher; Panaccione, Remo; Achkar, Jean‐Paul; El Ouali, Sara; Bruining, David; et al.
Summary: Background: Medical therapy and/or endoscopic balloon dilation with intralesional therapies are options for the treatment of small bowel fibrostenotic Crohn's disease (CD). Aim: To perform a systematic review summarising evidence for efficacy of systemic and endoscopic intralesional medical therapy in established small bowel strictures in adult CD patients. Methods: A systematic search of MEDLINE, EMBASE, CENTRAL and Scopus was conducted. Primary outcomes were rates of surgical resection and repeat endoscopic dilation. Pooled event rates from random effects models across studies with 95% confidence intervals were reported. Results: Ten studies describing systemic medical therapy and eight studies of intralesional injection were included. One randomised controlled trial each for systemic therapy and intrastricture injection were identified. Only observational studies were found for systemic biologic therapies, which exclusively included tumour necrosis factor (TNF) antagonists, while intralesional therapies all involved corticosteroids except for one study that evaluated infliximab. Pooled event rates for surgical resection after systemic and intralesional therapy were 28.3% (95% CI: 18.2%‐41.3%) and 18.5% (95% CI: 8.3%‐36.2%), respectively over a median follow‐up of 23 months (range 5.5‐105.8), and 21.8 months (range 5‐47). Risk of repeat endoscopic balloon dilation in those with intralesional therapy was 58.3% (95% CI: 36.6%‐77.3%) over a median follow‐up of 21.8 months (range 5‐47). Conclusions: There are no favoured therapies for patients with stricturing small bowel CD. Data are lacking for ustekinumab and vedolizumab. No endoscopic intralesional medications provided a clear benefit for prevention of repeat EBD or surgery.